The Effect of Dayak Onion Extract (Eleutherine palmifolia (L.) Merr) on Swimming Time and Oxidative Stress Levels in Mice with the Forced Swimming Test Model - Ramadhani, Aulia; Doewes, Muchsin; Listyawati, Shanti (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Excessive physical exercise can increase the occurrence of oxidative stress, which is characterized by cell damage caused by free radicals. Antioxidants found in Dayak Onion such as flavonoids, saponins, tannins, and vitamin C can be used as alternative ingredients to neutralize free radicals. The purpose of this study was to determine the effect of dose and duration of administration of Dayak onion extract on malondialdehyde (MDA) levels in a rat model of the forced gum test, extraction of Dayak onions using 96% ethanol. The type if research is Randomized Pre and Post Test Control Group Design. Male Sprague Dawley rats aged 2 months (weighing 150-200g) were divided into 5 groups: K- (control group, rats not given Dayak Onion extract but underwent forced swimming test), K+ (rats given xanthine and forced swimming test), P1 (rats given Dayak Onion extract at a dose of 50 mg/200 rats body weight/day), P2 (rats given Dayak Onion extract at a dose of 100 mg/200 rats body weight/day), P3 (rats given Dayak Onion extract at a dose of 200 mg/200 rats body weight/day). Dayak Onion extract was administered for 21 days with for 21 days with forced swimming test treatment, and changes in MDA levels were observed. The results showed that the administration of Dayak onion extract at a dose of 50 mg/200 rats/day, 100 mg/200 rats/day, and 200 mg/200 rats/day had an effect on preventing the increase in MDA, but at a dose of 200 mg/200 rats mice/day is the optimal dose. The conclusion is administration of Dayak Onion (Eleutherine palmifolia (L.) Merr) significantly decreased MDA levels in male Sprague Dawley rats with forced swimming test model.